2016
DOI: 10.2522/ptj.20150412
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of Instruments for Measuring of Lymphedema: Systematic Review

Abstract: Measurement instruments with evidence for good reliability and validity were BIS, water volumetry, tape measurement, and perometry, where BIS can detect alterations in extracellular fluid in stage 1 lymphedema and the other measurement instruments can detect alterations in volume starting from stage 2. In research, water volumetry is indicated as a reference test for measuring lymphedema in the upper extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 51 publications
3
115
2
5
Order By: Relevance
“…For example, a volume of 2000 mL in the affected upper extremity compared with 1915 mL in the unaffected upper extremity would be a ratio of 1.044 33. A recent systematic review of upper- and lower-extremity lymphedema assessment pooled data from multiple studies and found a standard error of measurement (SEM) for circumferential measurement of 2.8% and a smallest detectable change (SDC) of 6.6% 72. Thus, the 1.04 ratio, indicating a 4% difference between limbs, is above the SEM but is below the SDC and yet is within the calculated variance.…”
Section: Volume Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a volume of 2000 mL in the affected upper extremity compared with 1915 mL in the unaffected upper extremity would be a ratio of 1.044 33. A recent systematic review of upper- and lower-extremity lymphedema assessment pooled data from multiple studies and found a standard error of measurement (SEM) for circumferential measurement of 2.8% and a smallest detectable change (SDC) of 6.6% 72. Thus, the 1.04 ratio, indicating a 4% difference between limbs, is above the SEM but is below the SDC and yet is within the calculated variance.…”
Section: Volume Measuresmentioning
confidence: 99%
“…The literature was searched from January 1, 2000, through July 5, 2015; therefore, evidence from inception and newer articles may have been missed. For example, a recent systematic review of lymphedema measures72 was not included because of this limitation. Thus, it is important that clinicians also keep abreast of more recent additions to the literature.…”
Section: Limitationsmentioning
confidence: 99%
“…Mapping the lymph system is important in the diagnosis and treatment of lymphedema, especially for surgery interventions [28]. Through 68 Ga-NEB PET and MRL, morphologic and functional characteristics of lymphatic vessels in patients with lower extremity lymphedema were visualized.…”
Section: Resultsmentioning
confidence: 99%
“…Zur Quantifizierung von Beinveränderungen werden allem voran Umfangsmessungen durchgeführt [13][14][15] aus denen abschnittsweise Zustandsänderungen interpretiert werden. In der Literatur [16] wurden neben der CT-und MRT-Diagnostik verschiedene Methoden wie Wasserverdrängung und Perometrie zur Volumenverlaufskontrolle beschrieben. All diese Techniken sind jedoch mit eigenen Vor-und Nachteilen verbunden, folglich konnte sich keine Methode grundsätzlich durchsetzen.…”
Section: Hintergrundunclassified